Effects of biofouling on the sinking behavior of microplastics. (23rd November 2017) - Kaiser, David; Kowalski, Nicole; Waniek, Joanna J
Abstract: Although plastic is ubiquitous in marine systems, our current knowledge of transport mechanisms is limited. Much of the plastic entering the ocean sinks; this is intuitively obvious for polymers such as polystyrene (PS), which have a greater density than seawater, but lower density polymers like polyethylene (PE) also occur in sediments. Biofouling can cause large plastic objects to sink, but this phenomenon has not been described for microplastics <5 mm. We incubated PS and PE microplastic particles in estuarine and coastal waters to determine how biofouling changes their sinking behavior. Sinking velocities of PS increased by 16% in estuarine water (salinity 9.8) and 81% in marine water (salinity 36) after 6 weeks of incubation. Thereafter sinking velocities decreased due to lower water temperatures and reduced light availability. Biofouling did not cause PE to sink during the 14 weeks of incubation in estuarine water, but PE started to sink after six weeks in coastal water when sufficiently colonized by blue mussels Mytilus edulis, and its velocity continued to increase until the end of the incubation period. Sinking velocities of these PE pellets were similar irrespective of salinity (10 vs. 36). Biofilm composition differed between estuarine and coastal stations, presumably accounting for differences in sinking behavior. We demonstrate that biofouling enhances microplastic deposition to marine sediments, and our findings should improve microplastic transport models.